TPACK Self-Assessment Analysis on the Use of ‘Platform Merdeka Mengajar’ at ‘Teacher Learning Community’ of Indonesian State Vocational School - Fatriana, Nina; Hamidy, Fikri (Universitas Teknokrat Indonesia, 2025)
PMM or Platform Merdeka Mengajar (Merdeka Teaching Platform) is the Ministry of Education, Culture, Research and Technology ‘s 15th episode of Merdeka Belajar Policy to accompany the Emancipated Curriculum. It is a software application to be installed conveniently on teachers’ androids , functioning as teachers’ learning resource to improve their teaching performance the way the Emancipated Curriculum prescribed it, a means to share best practices , and lately a media to plan and carry out their annual work performance to be examined by the authorized body, as far as they have the belajar.id account to log in. However, beside remote distance and unavailability of internet which require infrastructure solution, bipolar demography of the teachers i.e. the digital native and digital immigrant teachers also leads to slow pacing progress use of PMM. This research was conducted to find out whether PMM gave positive influence on the teachers’ Teaching performance . The adapted TPACK self-assessment instrument was spread to 60 teacher members of Learning Community of SMKN 2 Kalianda , and structural equation modeling (SEM) was used to investigate the relations between those adapted TPACK subscales. The result showed that in the context of Teacher Learning Community at State Vocational High School 2 Kalianda , PMM digital technology (TK, PK, TPK) gave positive influence on the teachers’ teaching performance in terms of integrating technology in their lesson plans, learning materials,learning media, learning activities in terms of learning approach, learning strategies and learning models, and various stages of learning assessments as well as their professional development on their teaching major (TPACK).